Development Of Self-Healing Eco-Composite Materials Using Nano-Encapsulated Biopolymers For Green Construction Engineering - Verawati Itm (Journal of Advanced Engineering and Technology Research, 2025)
The growing demand for sustainable construction materials has accelerated the development of advanced eco-composites with enhanced durability, adaptability, and environmental compatibility. This study presents a novel self-healing eco-composite material engineered through the integration of nano-encapsulated biopolymers designed to autonomously repair microcracks and structural degradation. Utilizing a bio-based polymer matrix reinforced with cellulose nanofibers and embedded healing capsules containing chitosan–lignin nanoemulsions, the material exhibits a dual-function mechanism: crack initiation triggers capsule rupture, while the released bioactive agents polymerize to restore mechanical integrity. Experimental evaluation demonstrates a significant improvement in tensile recovery (up to 87%) and microcrack closure efficiency (92%) compared to conventional composites. Thermal stability and biodegradability assessments further confirm that the nano-encapsulated healing system enhances both performance and ecological compatibility, reducing long-term resource consumption and waste generation. The developed eco-composite shows strong potential for application in green construction engineering, particularly in structures requiring extended life cycles, reduced maintenance cost, and improved resilience against environmental stressors. This research contributes to advancing sustainable materials science by demonstrating a high-performance, self-healing composite built upon renewable biopolymer technology.